ANALISIS KEUNTUNGAN USAHA CAPTIKUS DI KELURAHAN PINARAS KOTA TOMOHON (Profit Analysis of Captikus' business in the Pinaras sub-district, Tomohon City) - Geiby Nikita Wawo; Jenny Baroleh; Jane Sulinda Tambas (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The objective of this research is to analyze the profits of the captikus businessÂ by using Revenue Cost Ratio Analysis in Pinaras Village, Tomohon City. This research was conducted from February 2021 to April 2021.The data collected is primary data by using direct interview techniques to captikus entrepreneurs as respondents. Secondary data were obtained from books, internet, thesis, journals and other sources related to this research. Sampling was Purposive Sampling samples by taking as many as 7 respondents.The results of research on captikus business in Pinaras Village, Tomohon City showed that this business is profitable with a total profit of Rp. 30,032,520 with an average of 4,290,360 for one month of production so that a one-time production total profit of Rp. 1,072,590. From the calculation of the R/C value obtained by 2.43 so that it can be concluded that the captikus business in Pinaras Village, Tomohon City is feasible to run.